Sam Ratulangi’s philosophical cultural ideas and their implications in the principle of just and civilized humanity - Pangalila, Theodorus; Loho, Ambrosius Markus; Tanase, Tasente (Jurnal Civics: Media Kajian Kewarganegaraan, 2022)
The article aims to explore the philosophical thinking of Si Tou Timou Tumou Tou (living human to humanize others) concerning the noble values contained in the second principle of the Pancasila, "Just and Civilized Humanity." The background of this paper is the development of the current era that erodes human existence from social man to individualist man. This article is library research by exploring the thoughts of Sam Ratulangi through relevant books and sources and looking for their relevance to the precept of Just and Civilized Humanity. The Si Tou Timou Tumou Tou is the most prominent Minahasan culture and animates the lives of the people of North Sulawesi in general and the people of the Tomohon city in particular. The values in the local wisdom of "Si Tou Timou Tumou Tou" are closely related to the fundamental values found in the second principle of Pancasila. The local wisdom of "Si Tou Timou Tumou Tou" and the second precept of Pancasila place human nature at an essential level in life.